Epidemiology and phylogeny of Haemonchus contortus through internal transcribed spacer 2 gene in small ruminants - Ahmad, Nisar; Khan, Saeed A.; Majid, Hafiz A.; Ali, Rehman; Ullah, Riaz; Bari, Ahmed; Akbar, Noor Ul; Majid, Abdul (Frontiers in Veterinary Science, 2024)
Haemonchus contortus (H. contortus) is a blood-feeding nematode causing infectious disease haemonchosis in small ruminants of tropical and subtropical regions around the world. This study aimed to explore the prevalence and phylogeny of H. contortus in small ruminants using the internal transcribed spacer-2 (ITS-2) gene. In addition, a comprehensive review of the available literature on the status of H. contortus in Pakistan was conducted. Fecal samples were collected from sheep and goats (n = 180). Microscopically positive samples were subjected to DNA extraction followed by PCR using species-specific primers. The overall prevalence of H. contortus was 25.55% in small ruminants. The prevalence of H. contortus was significantly associated with months and area. The highest occurrence of haemonchosis was documented in July (38.70%), whereas the lowest occurred in December (11.11%), with significant Formatted: Indent: Before: 0", Hanging: 0.13" differences. The prevalence was highest in the Ghamkol camp (29.4%) and lowest in the arid zone of the Small Ruminant Research Institute (17.5%) (P = 0.01). The results of the systematic review revealed the highest prevalence of haemonchosis (34.4%) in Khyber Pakhtunkhwa (P = 0.001). Phylogenetic analysis revealed a close relationship between H. contortus and isolates from Asia (China, India, Iran, Bangladesh, Malaysia, and Mongolia) and European countries (Italy and the United Kingdom). It has been concluded that H. contortus is prevalent in small ruminants of Kohat district and all over Pakistan, which could be a potential threat to foodproducing animals, farmers, dairy, and the meat industry. Phylogenetic analysis indicates that H. contortus isolates share close phylogenetic relationships with species from Asia and Europe.